Bounded Agency and Survival Strategies: Early Marriage Practices among Rohingya Muslim Refugees in Aceh - Sugitanata, Arif; Arif Sugitanata (Indonesian Journal of Sharia and Socio-Legal Studies, 2026)
This study is motivated by the emergence of early marriage practices among Rohingya Muslim refugees in Aceh, which are often normatively framed either as cultural traditions or legal violations, without sufficient attention to the structural conditions that shape them. Accordingly, this article aims to analyse the factors driving this practice and to examine how early marriage is rationalised within conditions of prolonged displacement. Employing a qualitative, fieldwork-based approach, the study was conducted at the Mina Raya refugee camp in September and December 2024 through direct observation and in-depth interviews with seven informants in order to capture the everyday dynamics of life under conditions of uncertainty. Drawing on Anthony Giddens’ structuration theory, the analysis focuses on the relationship between structural constraints and refugee agency. The findings indicate that early marriage is shaped by three interrelated conditions: insecurity within the camp environment, the perceived need to protect girls from harassment or violence, and the absence of viable alternatives such as formal protection mechanisms and access to education. Within this context, marriage is understood by families as the most immediate and rational means of securing safety and stability. The article argues that early marriage constitutes a form of bounded agency—a survival strategy enacted within a severely constrained field of choice shaped by legal invisibility, prolonged displacement, patriarchal norms, and unresolved trauma. These findings contribute to scholarship on Islamic law and socio-legal studies, while underscoring the need for clearer legal frameworks, stronger protection mechanisms, and expanded access to education for refugee women and girls. [Studi ini berangkat dari munculnya praktik perkawinan dini di kalangan pengungsi Muslim Rohingya di Aceh, yang sering kali dipahami secara normatif sebagai tradisi budaya atau pelanggaran hukum tanpa mempertimbangkan kondisi struktural yang melatarbelakanginya. Oleh karena itu, artikel ini bertujuan untuk menganalisis faktor-faktor yang mendorong praktik tersebut serta memahami bagaimana perkawinan dini dirasionalisasi dalam kondisi pengungsian yang berkepanjangan. Penelitian ini menggunakan pendekatan kualitatif berbasis kerja lapangan yang dilakukan di kamp pengungsian Mina Raya pada September dan Desember 2024 melalui observasi langsung dan wawancara mendalam terhadap tujuh informan, guna menangkap dinamika kehidupan sehari-hari dalam situasi ketidakpastian. Dengan menggunakan teori strukturasi Anthony Giddens, analisis difokuskan pada hubungan antara keterbatasan struktural dan agensi pengungsi. Hasil penelitian menunjukkan bahwa perkawinan dini dibentuk oleh tiga kondisi yang saling berkaitan, yaitu ketidakamanan di dalam kamp, kebutuhan untuk melindungi anak perempuan dari pelecehan atau kekerasan, serta ketiadaan alternatif yang memadai seperti perlindungan formal dan akses terhadap pendidikan. Dalam konteks ini, perkawinan dipahami oleh keluarga sebagai cara paling cepat dan rasional untuk memperoleh keamanan dan stabilitas. Artikel ini berargumen bahwa perkawinan dini merupakan bentuk bounded agency, yaitu strategi bertahan hidup yang dijalankan dalam ruang pilihan yang sangat terbatas akibat invisibilitas hukum, pengungsian berkepanjangan, norma patriarkal, dan trauma yang belum terselesaikan. Temuan ini berkontribusi pada kajian hukum Islam dan studi sosio-legal, serta menegaskan pentingnya penguatan kerangka hukum, mekanisme perlindungan, dan perluasan akses pendidikan bagi perempuan dan anak pengungsi.]